Stress redistribution due to creep in nimonic 90 ministry of aviation contract no. PD/28/021 report for the period January 1964 - June 1965: part 1 - Younger, A.; Clifton, T. E. (College of Aeronautics, 1965)
The period covered by this report has been devoted to the design, construction development and calibration of a special apparatus to simulate the stress redistribution conditions occurring during the creep of a cooled turbine blade. The experimental assembly consists of two creep machines, each operating at a different temperature, so controlled that a load is shared between them. maintaining equal creep strains (and in consequence equal creep rates) in each specimen. The stress in each specimen and the creep strain of the pair are automatically measured and recorded by a specially developed unit. Some preliminary results on an aluminium alloy are presented.